The effectiveness of using the Flipped Classroom Strategy in developing Creative Thinking Skills in Mathematics among First Intermediate Grade Female Students in Yanbu - Al-Thubyani, Haya Mousa Matrouk; Al-Barakati, Nevin Hamzah Sharaf (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to know the effectiveness of using the Flipped Classroom Strategy in developing creative thinking skills in mathematics among the first intermediate grade female students. The experimental approach was followed with a quasi-experimental design based on measurements (pre- post) to track the performance of two equal groups. The study sample consisted of (41) female students of the first intermediate grade female students, and the sample was divided into two groups, one experimental (21) student who studied using the flipped classroom strategy, and the other control (20) students who studied in the usual way, and the study tool was represented in the Torrance Test of Creative. The results of the study showed the appropriate creative thinking skills for the first intermediate grade students in mathematics, and proved that the level of creative thinking skills among the first intermediate grade female students is low, as well as the existence of statistically significant differences at the level of (α≥0.05) between the mean scores of the experimental group students and the scores of the disciplinary group students in the Torrance Test for Dimensional Creative Thinking. The findings were for the benefit of the students of the experimental group, as the results of the study demonstrated the great positive impact of the used strategy on developing creative thinking skills. In light of these results, the researcher made some recommendations, the most important of which are: Creating the appropriate educational environment to use the Flipped Classroom Strategy. directing the female teachers to develop creative thinking skills in a correct and balanced manner among students, and reconsidering the possibility of including of mathematics’ topics with creative activities.